The acute bronchiolitis rebound in children after COVID-19 restrictions: a retrospective, observational analysis - Curatola, Antonietta; Graglia, Benedetta; Ferretti, Serena; Covino, Marcello; Pansini, Valeria; Eftimiadi, Gemma; Chiaretti, Antonio; Gatto, Antonio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Bronchiolitis represents the main cause of illness and hospitalization in infants and young children. The aim of this study was to compare the Pediatric Emergency Department (PED) admissions for bronchiolitis during the post-COVID (Coronavirus disease) period to those of previous seasons and to analyze their etiology during COVID and post-COVID period. Methods: We compared demographics, clinical and microbiological data of children admitted to PED with bronchiolitis between September 2021 and March 2022 (post-COVID period) to the previous seasons (COVID and pre-COVID period). Results: During the post-COVID period the bronchiolitis season started earlier than usual, with a peak reached in November 2021; a gradual reduction was subsequently observed between December 2021 and January 2022. Our data showed a prevalence of High Priority code in children admitted to the PED with bronchiolitis during the post-COVID period (61.4%) compared the pre-COVID period (34.8%) (p=0.00). Also regarding the hospitalization of these patients, we found a major rate of hospitalization during this epidemic season (p=0.035). In addition, only 4 (1.5%) of the tested children resulted positive for SARS-CoV-2 and all of them were admitted to PED during the post-COVID period. The search for the other respiratory viruses showed during the current season a prevalence of respiratory syncytial virus (RSV) (60.2%), followed by Human Rhinovirus (30.1%). Conclusions: The post-COVID period was characterized by an early and short-term peak in acute bronchiolitis, with an increased rate of hospitalization. In addition, SARS-CoV-2 infection was rarely cause of bronchiolitis in children under 2 years old.